Rum för begravning. 1900-talets begravningskapell och krematorier - Karlsmo, Emilie (Svenskt gudstjänstliv, 1998)
The article deals with the specific room for the funeral ceremony—the burial chapel and the crematorium—as architecture, task of decoration, and room of farewell. Altogether, there are about 600 such buildings in Sweden, most of them having been built in the 20th century. The commissioner of the building is, with few exceptions, the Church or the ecclesiastical community (den kyrkliga samfälligheten). Up to the beginning of this century, the funeral ceremony took place in the graveyard, in connection with the Sunday service. During this century, the funeral ceremony has moved inside the church or to the above-mentioned buildings, and the funeral ceremony has become a service of it’s own. Connected with these changes is the fact that the cemeteries have been placed in the town outskirts, and the establishments of cremation. Other novelties are the so-called civil funeral ceremony—although it is so far being practised but to a small extent—and new faiths. The most important change from before is probably that the funeral service has turned into something personal and privatized, with only the closest family and a few guests attending. The burial chapel and the crematorium—the difference between them is of a technical nature concerning the incinerator— shall be at the disposal for every kind of funeral service, not only for Christian burials. The chapels/crematoriums are of extraordinary interest as expressions of the last century’s aesthetics, the attitude to death and grief and the changes in society. They are also very special as being a kind of public space: the individual user is not normally familiar with the building and will not become familiar with the architecture or the decorations. This leads to a demand for clarity and legibility. The entrance is a concrete example as being quite important, considering the many technical rooms and the fact that the same building often contains more than one chapel. This means, at a deeper level, a demand for a suitable room which has to work properly for all kinds of worshippers and other users, and which may at best also give sup port and hope. The article presents an exposition of burial chapels and crematoria through this century. The examples are representative and comparatively ordinary. The more distinguished examples, well-known in architectural history but considered solitaires in this context, are therefore omitted. They demonstrate the century’s styles and follow, for instance, the changes from the classicism of the 20’s to modernism, and later to the Swedish new-empiricism of the 40’s. The last two themes, although used differently, are of greater interest, namely the use of light and direction. Besides being a decorative motif, the theme of light appears as an illumination of the coffin or, by openings in the ceiling or on the walls, as a blaze of light. A popular motif throughout the century has been the concentration on the coffin, with all seats oriented towards it. There have, however, been complaints of feelings that everyone sits staring at the coffin. The colonnaded porch works, besides being a shelter, as an easily comprehended motif: it demonstrates the direction of the building, the entrance to the chapel. The survey demonstrates the search for a suitable symbolism of cremation. The crematorium plan (1938) in the town of Norrköping goes well along with the modernism interest for separating the functions, but it also represents the establishment of new ceremonies connected to the funeral service and cremation. There are, for instance, a chapel where to keep the remains, individual spaces for each coffin, a waiting-room for the family and the funeral guests, a room for the officiating clergy, and a separate room with an altar for the cinerary urn. It has been very important to end the cremation-funeral in a proper way; it was also quite important before the time when cremation became an established custom. The crematorium of Sandviken (1935) represents one of the very few realisations of the idea of the horizontal leaving of the coffin: a pair of huge doors would close, and so conclude the funeral service. Instead, the sinking of the coffin through the catafalque-lift became the most used and popular solution to conclude the burial of the coffin. Often electric fittings were added: the coffin would sink in light not in darkness— another example of the light motif. Today the normal conclusion of the cremation-funeral is that the funeral vivitors leave the coffin after the fare well and the blessing. One should, considering the decoration of the chapels, be very careful with statements of the cremation as a secularized custom and the decoration of these specific buildings as “funereal” or “secularized”. I am certain that a survey would show that the decorations are, both in style and motive, close to the decorations of contemporary churches, both corresponding in a wider context to the decoration with murals in public spaces. There was, however, clearly a change in the 1960’s. In connection with inaugurations, the possibility of using the chapel for other burials than Christian ones, and also the “neutral” symbolism of the decorations was stressed. One should bear in mind that this decade welcomed a public, more “open” art, also in churches. The change should therefore perhaps not be considered as characteristic for the decoration of the burial chapel or the crematorium, although there is clearly a change in the commissioners’ intentions and interpretations. The renovation and extension of the crematorium in Sandviken (1992) is typical for the today. The commissioner asked for an intimate room for ”personal” funerals. The extension comprises a small chapel with bright wood panels, thus creating an enclosed and light space. The coffin is to be placed in a flood of light under a lantern in the ceiling. The 36 seats are placed to face the coffin and the altar. The light motif here stands for concentration and hope, for an opening of interpretations, and perhaps at the same time also for a reluctance of expressing unambiguous meanings.